1996
DOI: 10.1111/j.1540-8175.1996.tb00872.x
|View full text |Cite
|
Sign up to set email alerts
|

Double Orifice Mitral and Tricuspid Valves

Abstract: Atrioventricular valve duplication is a rare congenital cardiac anomaly. The anomaly is usually recognized as an incidental finding at autopsy, open heart surgery, or two-dimensional echocardiography. In this article we present the transthoracic and transesophageal presentation of a case of mitral and a case of tricuspid valve duplication. The hemodynamic consideration of the lesions is discussed with a review of the literature. (ECHOCARDIOGRAPHY, Volume 13, January 1996)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In another case, the TV resembled a mass that consisted of a rudimentary valve and eventually led to TV surgery . Goldberg et al reported another case of an isolated DOTV with moderate TR . It is probable that mild regurgitation of a double orifice does not have a significant effect on outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In another case, the TV resembled a mass that consisted of a rudimentary valve and eventually led to TV surgery . Goldberg et al reported another case of an isolated DOTV with moderate TR . It is probable that mild regurgitation of a double orifice does not have a significant effect on outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Only two of 40 cases were diagnosed by preoperative echocardiography in our literature (Table 1). One possible explanation for this is an orthogonal relationship of the two orifices and filling jets made it difficult to visualize both orifices on a single conventional transthoracic view, as well as due to a lack of awareness of this condition 20 …”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the patients’ mortality or morbidity is due to other associated congenital anomalies 20 . While the reported number of isolated DOTVs was too small to allow for meaningful conclusions, 17 in only a few cases the DOTV led to a modification of the surgery performed for the additional congenital heart defects, 28 and the existence of a DOTV was responsible for a more severe clinical course of the patient 21,27,29,30 …”
Section: Discussionmentioning
confidence: 99%
“…Congenital anomalies of the mitral valve were detected in 0.5% of 13 400 subjects in echocardiographic studies . The usual anomalies of the leaflets are as follows: mitral valve prolapse, isolated cleft of the anterior valve leaflet, double orifice mitral valve, mitral ring, and Ebstein's malformation. The anomalies of the tensor apparatus are as follows: arcade or hammock valve, straddling mitral valve.…”
Section: Case Reportmentioning
confidence: 99%